State of Work on the Development of Agri-Environmental Indicators for Sustainable Development Purposes in Poland - Pacuszka, Robert; Kondraszuk, Tomasz (Stan prac nad konstrukcją wskaźników rolno-środowiskowych na potrzeby zrównoważonego rozwoju rolnictwa w Polsce, 2011)
This article describes specific problems of agricultural management. The idea and state of work on the development of agri-environmental indicators for monitoring the sustainable development of agriculture by the institutions responsible for payments and for the management of agri-environmental measures in Poland are presented. In the future, cost calculation will be based on 26 indicators currently being developed simultaneously by all EU member countries. In Poland, indicator data is gathered by the national statistics office. The existing sources for the indicators in the entire EU are currently being analysed by the Polish Institute of Technology and Life Sciences. The conclusion of this article is that efforts should be made to develop a cost calculation system that allows for considering economic, ecological and social objectives.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2011; Nr 177, s. 127-135
Keywords: agriculture; cost calculation; agri-environmental indicators; accounting; management